On a case Abetaglobulinemia and alterations Serum Beta-globulin during the Lupus Erythematosus - Stastny M., Pedro (1960)
During serial electrophoretic studies in SLE ​​patients, significant changes were observed in serum levels of beta-globulin fraction should be measured. The case of a patient who presented a transient globulinemia Abeta-, qu disappeared when Lupus was adequately treated with steroids and antimalarials is presented. The absence of the beta-globulin in the filter paper stained for protein with nearly normal beta fraction should be measured, disclosed by the method of moving boundaries (Tiselius) and presence of beta-lipoprmoteína curve suggests a lack of selective the stainable portion by Bromophenol Blue, this complex group of proteins. This case is compared with a previous case reported in the literature and probably related disorder nephrotic syndrome in our patient who suffered discussed.